Analisis Penerapan Sistem Informasi Manajemen (SIM) Dan Kebijakan Umum Tata Ruang Dalam Meningkatkan Pertumbuhan Ekonomi Di Kabupaten Purwakarta - Puspasari, Dewi Puspasari; Sukemi, Sukemi; Ismali, Dicky Taopik Ismali (Awatara Publisher, 2025)
This research aims to analyze the Application of Management Information Systems and General Spatial Planning Policies in Increasing Economic Growth in Purwakarta Regency. This research uses descriptive qualitative methods. The data sources in this research were obtained from field observations, interviews with sources and existing documentation. This research data analysis method uses data triangulation, the researcher combines data from observations, interviews and documentation and then makes conclusions. The research findings show that the implementation of the management information system in Purwakarta district is quite effective and efficient, although there are still several obstacles, but they can be overcome with the solutions offered. The description of spatial planning policies in Purwakarta district itself is in accordance with the characteristics and potential that exist in each region. Economic growth in Purwakarta district has increased every year in a better direction, even though in 2020-2021 it was hit by the Covid-19 pandemic, but economic conditions in Purwakarta district have returned to stability to date.